The Effect Of Parenting Stimulation Of Parents And Environments On Rude Motor Development In Garden Children 4-6 Years In The Mancar Village Area District Of Peterongan Jombang District - Farida, Siti Nur; Peristiowati, Yuly; Suhita, Byba Melda (Journal of Global Research in Public Health, 2019)
One important development is gross motoric, which is a body movement that uses large or most of the muscles or all parts of the body that are affected by the maturity of the child itself. This study aims to analyze the effect of parenting, parental stimulation and environment on gross motoric development in children of kindergarten aged 4-6 years in the District of Peterongan, Jombang. Quantitative research design with cross sectional approach. The study was conducted on January 7 to 9, 2019 with a population of 137 parents and a sample of 102 people with Cluster Random Sampling techniques. Data collection of independent variables with questionnaires and dependent variables with KPSP for aspects of gross or gross motoric motion DatOne important development is gross motoric, which is a body movement that uses large or most of the muscles or all parts of the body that are affected by the maturity of the child itself. This study aims to analyze the effect of parenting, parental stimulation and environment on gross motoric development in children of kindergarten aged 4-6 years in the District of Peterongan, Jombang. Quantitative research design with cross sectional approach. The study was conducted on January 7 to 9, 2019 with a population of 137 parents and a sample of 102 people with Cluster Random Sampling techniques. Data collection of independent variables with questionnaires and dependent variables with KPSP for aspects of gross or gross motoric motion Data analysis using logistic regression test. Based on the results of logistic regression statistics, the parenting variables p value 0.015, Stimulation of Parents p value 0.000 and environment p value 0,000, while jointly gross motoric development of children is influenced by parenting, stimulation of parents and environment significant p value 0,000 at Î± = 0.05 So it can be concluded that the gross motoric development of children is jointly influenced by parenting, parental and environmental stimulation, and environmental factors are the dominant factors in gross motor development in children of kindergarten aged 4-6 years in the District of Peterongan Regency Jombang. Because the environment is a very decisive factor whether or not the innate potential is achieved. A fairly good environment will enable the achievement of innate potential, while the less well will inhibit it. a analysis using logistic regression test. Based on the results of logistic regression statistics, the parenting variables p value 0.015, Stimulation of Parents p value 0.000 and environment p value 0,000, while jointly gross motoric development of children is influenced by parenting, stimulation of parents and environment significant p value 0,000 at Î± = 0.05 So it can be concluded that the gross motoric development of children is jointly influenced by parenting, parental and environmental stimulation, and environmental factors are the dominant factors in gross motor development in children of kindergarten aged 4-6 years in the District of Peterongan Regency Jombang. Because the environment is a very decisive factor whether or not the innate potential is achieved. A fairly good environment will enable the achievement of innate potential, while the less well will inhibit it.